PRAGMATIC REASONS FOR USING OXYMARONS IN DIALOGUES IN UZBEK AND ENGLISH - Aliyeva Shaxnoza Adxamjon qizi (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This paper investigates the pragmatic functions of oxymorons in dialogues across two linguistically and culturally distinct languages: Uzbek and English. Oxymorons, as rhetorical figures that juxtapose seemingly contradictory terms, serve diverse pragmatic roles in everyday and literary discourse. These include expressing irony, intensifying emotional nuance, conveying sarcasm, or encapsulating complex social commentary. By analyzing oxymoronic usage within dialogues from literature, media, and spontaneous speech, the study aims to uncover not just linguistic patterns but the underlying cultural worldviews they reflect. The contrastive approach reveals both universal pragmatic strategies and culturally specific meanings tied to oxymoronic expressions.